PHYSICO-CHEMICAL AND MICROSCOPIC STUDY OF ARJUNA (TERMINALIA ARJUNA) BARK - Chaudhary, *Satya Prakash; Kirtika, Dr; Kumar Singh, Anil; Ram, B. (International Journal of Ayurveda and Pharma Research, 2018)
In present study plant of Arjuna has been taken for physical and chemical analysis in terms of microtome of bark, powder study, loss on drying, ash values, extractive values, bulk density, Acid insoluble ash, Water-soluble Ash, Water-soluble extractive value, Alcohol-soluble extractive, pH range, TLC, Tapped density, Compressibility index, Hauser ratio, Angle of repose, Ultra violet fluorescence analysis of drug, etc. Physical and chemical analysis an important place in standardization of Ayurvedic drugs in order to make its global acceptability. The plant of Arjuna botanically named as Terminalia arjuna linn.; family Combretaceae, has traditionally been used to treat many diseases especially heart disease for centuries, thats why it is called as â€œGuardian of the heartâ€. Transverse sections of Arjuna bark shows the calcium oxalate crystal, starch grains and lignified cells respectively shows that Xylem Vessels, Sclerenchymatous Fibers, Cork Cells, Tracheids, Sclereids, LOD value of the sample of Arjuna is 5.63%. According to result the Arjuna has three Rf vaule0.70, 0.42, 0.28 table1.4. Angle of repose of powder sample shows the flow of powder. The extractive value of Arjuna have different solvent like water, ethanol, isopropanol, acetone, chloroform, benzene, toluene, petroleum ether, hexsene are respectively 50.80, 41.07,30.37, 8.95, 0.96, 0.67, 0.52, 0.51, 0.46.